一种基于描述函数的光伏并网系统稳定控制方法 (2022)
本发明涉及一种基于描述函数的光伏并网系统稳定控制方法，本发明在系统中设置稳定控制环，建立光伏并网系统模型线性部分传递函数，基于描述函数法建立系统非线性环节的描述函数。描述函数可以很好地分析非线性不连续环节引发的系统失稳问题，同时可以量化地计算临界稳定状态下系统振荡的幅值和频率。基于描述函数法的分析结果，提出一种稳定控制方法，控制参数可以根据电网强度对应调整，可以有效增强系统稳定性，避免发生振荡。 The invention relates to a photovoltaic grid-connected system stability control method based on a description function, and the method comprises the steps: setting a stability control ring in a system, building a linear part transfer function of a photovoltaic grid-connected system model, and building a description function of a nonlinear link of the system based on a description function method. The description function can well analyze the system instability problem caused by a nonlinear discontinuous link, and meanwhile, the amplitude and frequency of system oscillation in a critical stable state can be quantitatively calculated. Based on the analysis result of the description function method, a stability control method is provided, control parameters can be correspondingly adjusted according to the power grid